1995
DOI: 10.1111/j.1600-0684.1995.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐human gonadotropin antibodies generated during in vitro fertilization (IVF)‐related cycles: Effect on fertility of rhesus macaques

Abstract: Administration of human gonadotropins such as hFSH, hLH, and hCG to rhesus macaques can result in formation of anti-human gonadotropin antibodies. To determine whether the presence of these antibodies interferes with subsequent fertility, sixteen female rhesus macaques (Macaca mulatta) with known antibody levels were bred with male rhesus macaques. The presence of antibodies did not interfere with conception or maintenance of pregnancy. Furthermore, antibody titers did not increase during gestation or followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…Previously, when using natural hormones (e.g., human urinary FSH, hCG, equine chorionic gonadotropin) animals became refractory after only one cycle of stimulation (Bavister et al, 1986). It is likely that the monkeys produce antibodies and become less responsive to the exogenous gonadotropins in the repeat stimulation cycles (Ottobre and Stouffer, 1985;Bavister et al, 1986;Iliff et al, 1995;VandeVoort et al, 2003). This result was similarly to that reported by Wolf in 1999 (19.3/retrieval in initial cycle and 12.3/retrieval in repeat stimulation cycle).…”
Section: Effect Of Stimulation Cycle On or And Ivmsupporting
confidence: 79%
See 3 more Smart Citations
“…Previously, when using natural hormones (e.g., human urinary FSH, hCG, equine chorionic gonadotropin) animals became refractory after only one cycle of stimulation (Bavister et al, 1986). It is likely that the monkeys produce antibodies and become less responsive to the exogenous gonadotropins in the repeat stimulation cycles (Ottobre and Stouffer, 1985;Bavister et al, 1986;Iliff et al, 1995;VandeVoort et al, 2003). This result was similarly to that reported by Wolf in 1999 (19.3/retrieval in initial cycle and 12.3/retrieval in repeat stimulation cycle).…”
Section: Effect Of Stimulation Cycle On or And Ivmsupporting
confidence: 79%
“…Although IVM is still not fully optimized in all species, the birth of progeny following IVM, and then nuclear transfer, in sheep (Wells et al, 1997(Wells et al, , 1998b, pig (Betthauser et al, 2000), and goat (Keefer et al, 2001) establishes the feasibility of using IVM oocytes in these species. However, treatments of monkeys with exogenous gonadotropins especially HCG, can initiate an immune response, and eventually the animals no longer, respond to the human hormones (Ottobre & Stouffer, 1985;Bavister et al, 1986;Iliff et al, 1995;VandeVoort et al, 2003). To obtain multiple oocytes in macaques, female monkeys are treated with human gonadotropic hormones to induce development of multiple follicles .…”
Section: Somatic Cell Nuclear Transfer (Scnt) Is a Powerful Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…In humans and marmosets, oocytes can be collected repeatedly through ovarian stimulation by hFSH, and the collected oocytes contribute to in vivo development after in vitro fertilization or ICSI [20][21][22]. In rhesus monkeys, oocytes were obtained successfully from a second cycle of superovulation by hFSH [23]. Previously, we reported that oocytes were collected successfully after a second round of hFSH stimulation, but it was not known whether these oocytes could contribute to in vivo development after ICSI.…”
Section: Resultsmentioning
confidence: 99%